The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0081246317742246
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the sense of self of peer supporters using life design-related counselling

Abstract: This article explores the possible effects of group-based life design-related counselling on the sense of self of female adolescent peer supporters. Convenience and purposive sampling were used to select 24 participants at a private school (mean age = 16.5 years; standard deviation = 6.4 months). A parallel interactive mixed-method design, embedded in an intervention framework, was used to gather data. The Wilcoxon signed-rank test was used to compare pre- and post-test scores obtained on the Career Adapt-Abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Results of these studies have indicated positive client change, including increases in reflexive action (Hartung & Vess, 2016; Taylor & Savickas, 2016), self‐reflection (Cardoso, Gonçalves, Duarte, Silva, & Alves, 2016; Cardoso, Silva, Gonçalves, & Duarte, 2014; Hartung & Santilli, 2017), agency (Di Fabio, 2016; Maree, 2014; Taylor & Savickas, 2016), vocational certainty (Cardoso, Gonçalves, et al, 2016), self‐awareness (Maree, 2014, 2016a; Maree & Twigge, 2016), new career narratives that enhance quality of life (Setlhare‐Meltor & Wood, 2016), satisfactory work‐related contexts (Maree, 2015; Maree & Twigge, 2016), and willingness to deal more adaptively with career‐related challenges (Maree, 2016a). Research on life‐design group counseling and online group counseling has indicated similar changes for participants in the form of developing a unique sense of self (Maree, Pienaar, & Fletcher, 2018); fulfilling an identity (Barclay & Stoltz, 2016b); increasing career decision‐making readiness (Barclay & Stoltz, 2016a; Di Fabio & Maree, 2012); improving meaning making (Lengelle, Meijers, & Hughes, 2016); and elevating career certainty, career self‐efficacy (Cardoso, Janeiro, & Duarte, 2017), and career adaptability (Maree & Symington, 2015; Nota, Santilli, & Soresi, 2016). These studies were carried out in many countries and different cultural contexts, and the results were obtained from a diverse range of individuals.…”
mentioning
confidence: 99%
“…Results of these studies have indicated positive client change, including increases in reflexive action (Hartung & Vess, 2016; Taylor & Savickas, 2016), self‐reflection (Cardoso, Gonçalves, Duarte, Silva, & Alves, 2016; Cardoso, Silva, Gonçalves, & Duarte, 2014; Hartung & Santilli, 2017), agency (Di Fabio, 2016; Maree, 2014; Taylor & Savickas, 2016), vocational certainty (Cardoso, Gonçalves, et al, 2016), self‐awareness (Maree, 2014, 2016a; Maree & Twigge, 2016), new career narratives that enhance quality of life (Setlhare‐Meltor & Wood, 2016), satisfactory work‐related contexts (Maree, 2015; Maree & Twigge, 2016), and willingness to deal more adaptively with career‐related challenges (Maree, 2016a). Research on life‐design group counseling and online group counseling has indicated similar changes for participants in the form of developing a unique sense of self (Maree, Pienaar, & Fletcher, 2018); fulfilling an identity (Barclay & Stoltz, 2016b); increasing career decision‐making readiness (Barclay & Stoltz, 2016a; Di Fabio & Maree, 2012); improving meaning making (Lengelle, Meijers, & Hughes, 2016); and elevating career certainty, career self‐efficacy (Cardoso, Janeiro, & Duarte, 2017), and career adaptability (Maree & Symington, 2015; Nota, Santilli, & Soresi, 2016). These studies were carried out in many countries and different cultural contexts, and the results were obtained from a diverse range of individuals.…”
mentioning
confidence: 99%
“…Programs based on self-mastery and self-awareness principles are particularly effective during adolescence as they help define who they truly are and surface values, talents and purpose. Once those programs are formulated and implemented, future research endeavors could be oriented toward the sustainability of those programs' benefits throughout life (Maree, Pienaar & Fletcher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, lack of proper training of peer supporters has been found to have a negative effect on peer led psychosocial support groups in schools (Mitchell, Purcell, Forsyth, Barry, Hunter, Simpson & Moore,2020). In America, lack of training on the part of peer supporters negatively affects psychosocial support program evaluation (Maree, Fletcher & Pienaar, 2018). Moreso, in Uganda, Zimbabwe, Botswana and South Africa several educational planners and heads of institutions are not trained to assist peer led groups in psychosocial support programs (Mtemeri, 2020).…”
Section: Trainingmentioning
confidence: 99%